Law Enforcement Challenges In Forest Destruction: Evidence from Batam City - Andika Saputra; Winsherly Tan (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2023)
Forests are a priceless gift and mandate from God Almighty and one that must be grateful for. Forests are a national development capital that has ecological, socio-cultural benefits and influences economic conditions as well as trade and industry conditions. Damage to the Batam City forest area due to illegal logging and theft of forest products and causing huge losses, so there is a need for a very fast handling. The problems studied in this research are forest protection arrangements and challenges to forest destruction law enforcement in Batam City. This study uses normative legal research methods. Normative legal research or library research is research that examines document studies, namely using various secondary data such as laws and regulations, court decisions, legal theories, and can be in the form of opinions of scholars. The results of the research show that law enforcement against forest protection Law Number 41 of 1999 concerning Forestry in exercising its authority to protect forests is carried out in a preventive and repressive manner.